Sanguinarine, Isolated From Macleaya cordata, Exhibits Potent Antifungal Efficacy Against Candida albicans Through Inhibiting Ergosterol Synthesis - Hu, Ziwei; Hu, Hao; Hu, Zhili; Zhong, Xiaojun; Guan, Yifu; Zhao, Yunshi; Wang, Lu; Ye, Liang; Ming, Liliang; Riaz Rajoka, Muhammad Shahid; He, Zhendan; Wang, Yan; et al. (Frontiers in Microbiology, 2022)
In recent decades, infections caused by the opportunistic fungus Candida albicans have increased, especially in patients having immunodeficiency. In this work, we demonstrated the capability of sanguinarine (SAN) to counteract C. albicans in vitro and in vivo, and explored the possible mode of action. SAN exhibited antifungal activity against C. albicans clinical isolates with MICs at the range of 37.5-50 μg/mL. Scanning electron microscopy and transmission electron microscopy further showed that SAN induced morphological changes and structure disruption to C. albicans cells, such as masses of cellular debris, ruptured cell wall, membrane deformation. Flowcytometry revealed that SAN could lead to cell membrane damage, docking analysis suggested that SAN may bind to CYP51, and thereby cause above 90% ergosterol content reduction by ergosterol content analysis. Further, we validated the efficacy of SAN against candidiasis caused by C. albicans in a murine model, and SAN significantly improved survival and reduced weight loss compared to vehicles. The treatment of 1.5 and 2.5 mg/kg/d SAN obviously reduced the fungal burden in kidney. Besides that, no fungal cells were observed in the tissues of lung and kidney after SAN treatment by histopathological examination. This study suggests that SAN is a promising plant-derived compound for developing an effective anticandidal agent.